Empowering Students through Congregational Leadership: A New Approach to Character Education in Islamic Boarding Schools - Toto Santi Aji; Heramb Kulkarni (Al-Tanzim: Jurnal Manajemen Pendidikan Islam)
This study aims to analyze the implementation of collective leadership in character education and its impact on students' attitudes and behavior in Islamic Boarding Schools. This study is based on integrating the interpretation of the Fii Zhilalil Quran with the model of collective leadership in character education, especially in formal education. The qualitative research method with a case study approach involves data collection techniques through interviews, observations, and documentation. Data analysis was done using a thematic approach, grouping interviews, observation, and documentation data based on relevant categories to find the central theme. The study results indicate that the implementation of collective leadership in character education has succeeded in increasing the values of cooperation, mutual respect, and responsibility in students. This collective leadership model is applied in formal and non-formal activities such as cooperation, providing direct experience in developing social and leadership skills. The social implications of this study are the importance of implementing a religious-based leadership model to shape students' characters who can contribute positively to society.